The uncertain sciences - Mazlish, Bruce, 1923-2016 (Yale University Press, 1998)
In this wide-ranging book one of the most esteemed cultural historians of our time turns his attention to major questions about human experience and the attempts to understand it "scientifically." Bruce Mazlish considers the achievements, failings, and possibilities of the human sciences - a domain that he broadly defines to include the social sciences, literature, psychology, and hermeneutic studies. In a synthesis built upon the work of earlier philosophers and historians, Mazlish constructs a new view of the nature and meaning of the human sciences